PENGETAHUAN REMAJA PUTRI TENTANG DAMPAK PERNIKAHAN DINI BAGI KESEHATAN REPRODUKSI - Evita Syefinda Putri (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2020)
Introduction In today’s era, we still encounter many early marriages (marriage to adolescents under the age of 20). One of the reasons is the lack of knowledge about the impact of early marriage on reproductive health. Without them realizing that early marriage can have a big impact on reproductive health (especially the uterus) is not yet perfect, leading to abortion or miscarriage. The purpose of this study was to determine the knowledge of young women about the impact of early marriage on reproductive health. Methode This study used a descriptive research design conducted at RW 07, Pandanwangi Sub-District, Malang on 11 – 20 December 2020 with an average monthly population of 65 young women and a sample of 40 young women. Sampling used was accidental sampling. Data analysis using univariate analysis. Questionnaire measurement tools and data processing in the form of editing, coding, scoring, tabulating, and percentage. Results The results showed half of them had less knowledge about the impactof early marriage on reproductive health as many as 20 respondents (50%), nearly half had good knowledge as many as 12 respondents (30%), and a small proportion had sufficient knowledge as many as 8 respondents (20%). These results are most likely due to factors that influence knowledge, namely age, education and sources of information. Conclusion Seeing the results of this study, it is hoped that young women will be more active in participating in extension activities in order to increase knowledge about the impact of early marriage on reproductive health. Keywords: Young Women Knowledge, Early Marriage, Health Reproduction